A Case Study of Wet Soil Mixing for Bearing Capacity Improvement in Turkey - Arash Maghsoudloo; Asli Can (Deep Foundations Institute, 2014)
"Abstract This paper presents a ground improvement implementation case under a raft foundation of a local hospital. The selected ground improvement method is Wet Soil Mixing (WSM) technique. Soil mixing is increasingly applied to environmental applications and ground stabilization in geotechnical projects. In this technique, weak soil is mixed with cementitious slurry to improve the characteristics of the soil. The investigated case is one of the pioneering WSM ground improvement technique implementation cases in Turkey. The soil profile is mainly consisted of low plasticity clay. The effect of ground improvement is verified by a series of laboratory tests and four in-situ pile loading tests. The results of in-situ pile load tests on constructed soilcrete columns showed an acceptable factor of safety for the bearing capacity of the WSM columns. Measured bearing capacities in all four tested columns were nearly 20% higher than calculated values. In addition, a set of samples are obtained from the constructed columns and unconfined compression tests have been conducted. The laboratory test results indicate that the selected cementitious slurry has a sufficient efficiency to form the stabilizing columns.IntroductionIn the construction industry, stabilization of the soft ground by lime or cement stabilization is a widely used technique. In ground improvement systems deep mixing method (DMM) results in the same stabilization in deep portions of the soft soil profile by mixing cementitious slurry by means of mechanical augers. The pioneering cases of modern deep mixing application can be traced back to the year 1970 that was used for the stabilization of marine soils below the water level for the construction of harbor structures (Terashi et al., 1979). Nowadays, DMM is shown to be a proper and efficient method for the foundation of the structures and embankments on land. Some recent studies also reported that reasonable settlement reduction range in the stabilized soils under the foundation of structures (Archeewa et al., 2011). In addition to reduction of the structural settlement under service loads, deep mixing methods are also utilized when there is a concern with contaminated soil and groundwater or groundwater control (Andromalos and Bahner, 2003).Although, the DMM is shown to be a successful method in numerous studies for improvement of a wide range of soil types such as organics, fine-grained, and coarse grained material, it has some limitations (Archeewa et al. 2011, Jameson et al. 2010, Jelisic and Leppanen 2004, Lambrechts and Roy 1997, Meyersohn 2007, Miki and Nozu 2004, Olsson et al. 2008, O’Rourke and McGinn 2004, Stewart et al. 2004, Yang et al. 2011). High soil density and stiffness could damage deep mixing rigs. Engineering properties of the soilcrete columns changes based on the soil type, water content and other factors such as organic content of the available soil profile, so properties of the generated soilcrete should be verified by a set of rigorous testing procedures (Puppala et al. 2004).Based on the general classifications presented in the ground improvement literature, deep soil mixing method is divided into two main types of dry or wet mixing methods. In the dry and mixing methods compressed air and water are utilized as the binder transporter medium respectively (Moseley and Krisch, 2004). In addition, DMM methods can be categorized based on the employed mixing methods during the construction. In this study, the main aim is to present and elaborate on the selected method is known as Wet Speed Soil Mixing (WSSM)."